Meditations on first philosophy : with selections from the Objections and replies - Descartes, René (Oxford University Press, 2008)
'It is some years now since I realized how many false opinions I had accepted as true from childhood onwards...I saw that at some stage in my life the whole structure would have to be utterly demolished'